2021
DOI: 10.3892/etm.2021.10792
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological effects of Picrasma quassioides (D. Don) Benn for inflammation, cancer and neuroprotection (Review)

Abstract: Picrasma quassioides (D. Don) Benn is an Asian shrub with a considerable history of traditional medicinal use. P. quassioides and its extracts exhibit good therapeutic properties against several diseases, including anti-inflammatory, antibacterial and anticancer effects. However, the composition of compounds contained in P. quassioides is complex; although various studies have examined mixtures or individual compounds extracted from it, studies on the application of P. quassioides extracts remain limited. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…As an effective biological ingredient, β-CCE is widely present in P. quassioides, human urine, and the brain (28,29). The beneficial effects of β-CCE on panic disorders, anxiety, and other social behaviors were recognized through neuropsychopharmacological studies in the 1880s (30).…”
Section: Discussionmentioning
confidence: 99%
“…As an effective biological ingredient, β-CCE is widely present in P. quassioides, human urine, and the brain (28,29). The beneficial effects of β-CCE on panic disorders, anxiety, and other social behaviors were recognized through neuropsychopharmacological studies in the 1880s (30).…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive compounds in GMP were quassin and picrasin B (Figure 7A) [18]. Figure 7B presents chromatograms of two standard compounds.…”
Section: Quantification Of Chemical Constituents In Gmpmentioning
confidence: 99%
“…GMP has been used to treat several symptoms, such as indigestion, gastroenteritis, pulmonary tuberculosis, and eczema [16,17]. The main components of GMP are quassinoids, triterpenoids, and alkaloids, which have a range of pharmacological effects, including anti-inflammatory, anti-cancer, and neuroprotective effects [18]. Previous studies reported that the GMP extract inhibited the allergic response in an ovalbumin-induced mouse model of asthma and suppressed the production of inflammatory mediators in RAW264.7 macrophages stimulated with lipopolysaccharide (LPS) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…β-carboline alkaloids extracted from natural herbs exhibit many pharmacological effects in medical treatment that differ based on the part of the plant and species from which they have been extracted 3 . Ethyl β-carboline-3-carboxylate (β-CCE) belongs to a class of β-carboline alkaloids extracted from Picrasma quassioides 3 . This kind of alkaloid has anti-inflammatory, anti-viral 4 , anti-oxidative 5 , anti-tumour, and calming effects on brain nerves 6 .…”
Section: Introductionmentioning
confidence: 99%
“…β-carboline alkaloids extracted from natural herbs exhibit many pharmacological effects in medical treatment that differ based on the part of the plant and species from which they have been extracted [3]. Ethyl β-carboline-3-carboxylate (β-CCE) belongs to a class of β-carboline alkaloids extracted Ivyspring International Publisher from Picrasma quassioides [3].…”
Section: Introductionmentioning
confidence: 99%